(untitled) (Third Sector Social Economic Review, 2021)
Artificial intelligence has much more importance beyond just being another technological tool of the 21st century, such as autonomous weapons systems, automobiles, or robots in international relations. These systems, which are being integrated into various mechanisms swiftly, affect decision-making processes radically and even replacing humans as non-human actors. This paper gives contemporary examples of these systems’ potential roles in decision-making and policy mechanisms in the near future and argues their differences, limits, and capabilities from social sciences’ perspective. In addition, these system’s non-human intelligent thought processes are discussed together with drawbacks they bring, emphasizing their current and imminent impacts on international relations.